EFEKTIVITAS PENERAPAN TIMBANG TERIMA, PRECONFERENCE, POSTCONFERENCE SESUAI DENGAN SOP DI RUANGAN UNIT STROKE DAN YOSEP PAVILIUN RUMAH SAKIT - yanti Rosdiana; Neni Maemunah; Arie Jefri Ka’arayeno (Jurnal Salingka Abdimas, 2021)
ABSTRACTWeighing and accepting patients is one form of nurse communication in carrying out nursing care for patients. Weighing in patient acceptance is designed as a method to provide relevant information to the nursing team at every shift change, as a practice guide to provide information about the patient's current condition, treatment goals, treatment plans and determine service priorities. The stroke unit room and the Yosep Pavilion Room at the Waluyo Pavilion Hospital have implemented a weigh-in and weigh-in is only done at the nurse station. Weigh-and-accepts are carried out as a whole or combined, starting from preconference, midleconferance and postconference. Methods: providing SOPs for weighing and receiving according to the stages in the literature, providing video explanations of the implementation of weigh-in, pre-conference, middle-conferance and post-conference. Results: the weigh-in, pre-conference, mid-conference and post-conference were carried out separately and nearly 80% of the 25 nurses in the stroke unit and Joseph pavilion were able to differentiate between weigh-in, preconference, middle and post conference processes. With this understanding, it is expected to prevent errors during weigh-in, pre-conference, post-conference and of course improve the quality of nurse service quality. Keywords: Effectiveness, weigh-in, preconference, postconference  ABSTRAK Timbang terima pasien merupakan salah satu bentuk komunikasi perawat dalam melaksanakan asuhan keperawatan pada pasien. Timbang terima pasien dirancang sebagai salah satu metode untuk memberikan informasi yang relevan pada tim perawat setiap pergantian shift, sebagai petunjuk praktik memberikan informasi mengenai kondisi terkini pasien, tujuan pengobatan, rencana perawatan serta menentukan prioritas pelayanan. Ruangan unit stroke dan Ruang Yosep Paviliun RS panti Waluyo sawahan telah menerapkan timbang terima dan timbang terima hanya dilakukan di nurse station. Timbang terima yang dilakukan secara keseluruhan atau digabung mulai preconferance, midleconferance dan postconferance. Metode: memberikan SOP timbang terima sesuai tahapan di literature, memberikan penjelasan video pelaksanaan timbang terima, preconferance, midleconferance dan postconferance. Hasil: pelaksanaan timbang terima, preconferance, midleconferance dan postconferance dilakukan secara terpisah serta hampir 80% dari 25 perawat yang ada di unit stroke dan yosep paviliun dapat membedakan proses timbang terima, preconference, middle dan post coferance. Dengan pemahaman tersebut diharapkan mencegah terjadinya kesalahan saat timbang terima, preconferent, postconferent dan tentunya meningkatkan kualitas mutu pelayanan perawat. Kata Kunci : Efektifitas, timbang terima, Preconference, postconference